(untitled) (Ustozlar uchun, 2026)
This article is about perspectives of curriculum, meaning of syllabus and difference between curriculum and syllabus. It is also about principles of curriculum construction. This is because these principles help you when you yourself are up to the task of curriculum development. From B.Ed. point of view this topic comes in the study of pedagogy of various subjects and under subject Knowledge and curriculum.